A Logical Method to Estimate Reliability of Quantum Communication Channels - Abbas, Jabbar; Abhang, Ranjana (Al-Nahrain Journal of Science, 2011)
In this paper, we propose mathematical framework “Fuzzy three-valued measure and logical fuzzy integral” based on the three-valued logic. Then, we establish a simple model for representing quantum states and vagueness in transmission caused by noise, and we apply the proposed mathematical framework as a logical method to estimate reliability of quantum communication channels approximately.